Evaluasi Fatwa Hukum Tubektomi Melalui Pendekatan Baru “Manhaj Bermazhab” - Rohman, Fathur; Zuhri, Hilmi Husaini (Syariah: Journal of Fiqh Studies, 2024)
Tubectomy, a permanent contraceptive procedure, generates debate within Islamic law concerning its validity. This study aims to evaluate the legality of tubectomy using a mazhab-based approach through the takhrij method, which is a method for deriving legal rulings from the perspective of Islamic schools of thought. The research critiques views permitting tubectomy based on changes in legal rulings due to changes in 'illat and maslahat mursalah, and compares the fatwas of the Indonesian Ulema Council (MUI), Nahdlatul Ulama (NU), and academic perspectives from Fitri A.N., Akhmad Farid M.S., and Herlina Utami. A qualitative descriptive-analytical method is employed to analyze various sources, including classical fiqh texts and contemporary fatwas. The findings indicate that tubectomy is deemed haram and that the success of rekanalisasi does not alter this ruling. The consistency of this prohibition is based on the fact that reproductive organs cannot return to their natural function without medical intervention, thereby violating Islamic contraceptive principles. This conclusion supports the fatwa of NU which asserts the prohibition of tubectomy and rejects views allowing it under the condition of rekanalisasi. The study offers an in-depth understanding of the legal status of tubectomy and invites further discussion on contraceptive methods within modern Islamic jurisprudence.